2001
DOI: 10.1111/j.1572-0241.2001.03862.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between esophageal dysfunction and neuropathy in diabetic patients

Abstract: Esophageal motility disorder and abnormal acid reflux were related to DMN in diabetic patients. A significant correlation was found between esophageal dysfunction and MCV. However, no significant correlation was found between esophageal dysfunction and CVRR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 30 publications
2
38
0
1
Order By: Relevance
“…CV R-R is a simple index of diabetic autonomic neuropathy, in particular of vagal neuropathy, and a CV R-R value of 2% has been recognized as a critical level for vagal neuropathy [31,32]. The vagal nerve conveys ghrelin-mediated signals for GH secretion and food intake from the stomach to the brain [33].…”
Section: Discussionmentioning
confidence: 99%
“…CV R-R is a simple index of diabetic autonomic neuropathy, in particular of vagal neuropathy, and a CV R-R value of 2% has been recognized as a critical level for vagal neuropathy [31,32]. The vagal nerve conveys ghrelin-mediated signals for GH secretion and food intake from the stomach to the brain [33].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that disease duration of diabetes [117,120] and the presence of diabetic neuropathy [119,120] were associated with GERD. Because esophageal motility disorder and abnormal acid reflux in diabetic patients are associated with diabetic motor neuropathy [122] and such esophageal dysfunction is worsened with long disease duration [123], esophageal dysfunction may result in a higher prevalence of GERD in diabetic patients.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…2 In our study, esophageal dysfunction was unexpectedly found to be related to motor nerve conduction velocity rather than the coeffi cient of variation of R-R intervals, although the pathophysiology of esophageal dysfunction was largely caused by autonomic neuropathy. 2 It may be hard to predict esophageal dysfunction in patients with diabetes screened for autonomic neuropathy based solely on cardiac dysfunction because the degree of vagal disorder varies by organ in patients with diabetes. [3][4][5][6] There are many opinions on the relationship between obesity and GERD; for example, obesity is a risk factor for GERD.…”
Section: Authors' Replymentioning
confidence: 52%